2006
DOI: 10.1002/jcb.20773
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β2 stimulates cranial suture closure through activation of the Erk‐MAPK pathway

Abstract: Cranial sutures are important growth sites of the skull. During suture closure, the dura mater is one of the most important sources of various positive and negative regulatory signals. Previous results indicate that TGF-beta2 from dura mater strongly accelerates suture closure, however, its exact regulatory mechanism is still unclear. In this study, we confirmed that removal of dura mater in calvarial organ culture strongly accelerates sagittal suture closure and that this effect is further enhanced by TGF-bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
1
27
0
1
Order By: Relevance
“…Importantly, ERK MAP kinase was also suggested to crosstalk with TGF-b signaling pathway components (Hayashida et al 2003;Lee et al 2006;Fujita et al 2004). Our data of immediate ERK1/2 signal activation in TGF-b stimulated IEC-6 cell differentiation are consistent with data acquired from other cell types.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, ERK MAP kinase was also suggested to crosstalk with TGF-b signaling pathway components (Hayashida et al 2003;Lee et al 2006;Fujita et al 2004). Our data of immediate ERK1/2 signal activation in TGF-b stimulated IEC-6 cell differentiation are consistent with data acquired from other cell types.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that TGF-b2 and TGF-b3 were highly expressed in SHED compared with DPSCs. Because TGF-b2 has been reported to stimulate cell proliferation and collagen synthesis (26,27), it might regulate the biological activities of SHED. In addition, CTGF, whose expression was higher in SHED, is a matrix signaling molecule involved in TGF-b-induced cell proliferation, matrix synthesis, angiogenesis, migration, and osteoblast lineage differentiation of MSCs (28).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of FGF-2 could imply a dedifferentiation or a reversal of emphasis on cell proliferation rather than bone mineralization in differentiating hMSCs [36]. Moreover, an increase in TGF-b expression, in association with SMAD 3, could also hinder ALP activity and mineralization in osteoblasts [37] thereby promoting cell growth for a vast potential in many bone tissue regeneration strategies [38,39] (Fig. 7).…”
Section: Carboxyl Functionalizationmentioning
confidence: 95%